Democratizing education at the margins: faculty and practitioner perspectives on delivering online tertiary education for refugees - Thomas M. Crea; Neil Sparnon (International Journal of Educational Technology in Higher Education, 2017)
Abstract Online distance learning is rapidly becoming a mainstay in higher education. Yet, there still exists unequal access to internet technology among the world’s most vulnerable populations. This article reviews the implementation of an online pilot program that provided tertiary education to refugees in Africa and the Middle East, using a unique blend of brick-and-mortar and virtual instruction. Faculty experiences mirrored much of the experiences of instructors in more traditional online education – while onsite staff provided a unique perspective on the embedded nature of the program, based in local contexts. The results of this study helped point the way towards important program modifications to increase the quality of faculty communication and the cultural relevance of the curriculum. Future research is needed to identify whether such programs lead to improved outcomes for refugees.